Sex-biased immunological processes drive hidradenitis suppurativa - Young, Kelly Z.; Dimitrion, Peter; Zhou, Li; Adrianto, Indra; Mi, Qing-Sheng (Frontiers in Immunology, 2023)
Hidradenitis suppurativa (HS) is a chronic inflammatory skin condition that can manifest with abscesses, sinus tracts, and scarring in the intertriginous areas of the body. HS is characterized by immune dysregulation, featuring elevated levels of myeloid cells, T helper (Th) cells, and pro-inflammatory cytokines, particularly those involved in Th1- and Th17-mediated immunity. In most epidemiological studies, HS shows a strong female sex bias, with reported female-to-male ratios estimated at roughly 3:1, suggesting that sex-related factors contribute to HS pathophysiology. In this article, we review the role of intrinsic and extrinsic factors that contribute to immunological differences between the sexes and postulate their role in the female sex bias observed in HS. We discuss the effects of hormones, X chromosome dosage, genetics, the microbiome, and smoking on sex-related differences in immunity to postulate potential immunological mechanisms in HS pathophysiology. Future studies are required to better characterize sex-biased factors that contribute to HS disease presentations.